The C-terminal 79 amino acids of the herpes simplex virus regulatory protein, Vmw65, efficiently activate transcription in yeast and mammalian cells in chimeric DNA-binding proteins. - Cousens, D; Greaves, R; Goding, C; O'Hare, P (1989)
Activation of herpes simplex virus immediate early gene expression normally requires the formation of a ternary complex between a virus trans-activator, Vmw65, a cellular octamer-binding protein, TRF and the cis-acting target sequence, the TAATGARAT motif. We report that the C-terminal 79 amino acids of Vmw65, which contain a potential acidic amphipathic helix, can activate transcription in both yeast and mammalian cells in the absence of TRF interaction when fused to the DNA-binding domain of the yeast transcription factor, GAL4. Together with our previous report which showed that the recruitment of TRF to the DNA by Vmw65 is insufficient for transcription activation, these results indicate that the octamer binding protein may not be directly involved in transcriptional induction mediated by Vmw65. The TRF-Vmw65 complex may therefore represent a novel class of transcription activator in which the protein domain responsible for sequence-specific DNA binding, present in TRF, and that necessary for induction of transcription, within Vmw65, are located on separate proteins. These results are discussed with reference to combinatorial transcriptional control and the role of octamer-binding proteins in other systems.